2015
DOI: 10.12738/estp.2015.5.2505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Differential Item Functioning on Test Equating

Abstract: This study examines the effect of differential item functioning (DIF) items on test equating through multilevel item response models (MIRMs) and traditional IRMs. The performances of three different equating models were investigated under 24 different simulation conditions, and the variables whose effects were examined included sample size, test length, DIF magnitude, and the test type. The MIRMs, in which the DIF factors were added as parameters, were compared with the Stocking-Lord (SL) method (one of the IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The purpose of this simulation study was to investigate the performance of linking methods in the two-group case for the 2PL model under different sample sizes, different numbers of items, and different amounts of uniform and nonuniform DIF. Most simulation studies either assume invariant item parameters (i.e., no DIF) or presuppose partial invariance in which only a few item parameters differ between groups (e.g., [63,[105][106][107][108][109][110][111][112]). There is a lack of research in the presence of random DIF, although there is some initial work for continuous items [88,89].…”
Section: Purposementioning
confidence: 99%
“…The purpose of this simulation study was to investigate the performance of linking methods in the two-group case for the 2PL model under different sample sizes, different numbers of items, and different amounts of uniform and nonuniform DIF. Most simulation studies either assume invariant item parameters (i.e., no DIF) or presuppose partial invariance in which only a few item parameters differ between groups (e.g., [63,[105][106][107][108][109][110][111][112]). There is a lack of research in the presence of random DIF, although there is some initial work for continuous items [88,89].…”
Section: Purposementioning
confidence: 99%
“…Tests of sex invariance with the bifactor model indicated that item loadings for the common factor showed significant violations of both metric and scalar invariance (see Table 1). Violations of invariance assumptions can in principle bias scores and score equating (Kabasakal & Kelecioğlu, 2015), but statistically significant bias may not in fact be strong enough to make a practical difference (Wanders et al, 2015). To assess the seriousness of these violations, we used Mplus to calculate empirical Bayes estimates of the common factor scores for the basic single factor model and the configural model, regressing the former on the latter separately for females and males.…”
Section: Testing Construct Equivalence In Measures Of Youth Depressionmentioning
confidence: 99%